Morphological and Electronic Characteristics of Nanoalumina Alone and in High-Temperature (Fumed) and Low-Temperature (Mechanical) Mixtures with Nanosilica - Ya. V. Zaulychnyy; V. Ya. Ilkiv; V. I. Zarko; M. V. Karpetz; M. V. Pereginiak; S. S. Petrovska; V. M. Gun'ko (Хімія, фізика та технологія поверхні, 2014)
Crystalline and electronic structures of nanoalumina alone and in different mixtures with nanosilica have been analyzed using X-ray diffraction (XRD) and ultrasoft X-ray emission spectroscopy (USXES). Narrowing of the OK?bands of crystalline alumina occurs with decreasing nanoparticle size. Electron transfer from oxygen to aluminum atoms due to Al–O bond breakage under irradiation leads to occupation of high-energy 3d level of Al. In nanoparticles, the Al–O bond strength and O–O interactions enhanced by Laplace (bubble) pressure lead to ? phase stabilizing if coherent-scattering region size (dCSR) reaches 7 nm which is smaller than that for ? phase (dCSR = 11–20 nm) of alumina and silica/alumina studied. The dCSR values are in agreement with nanoparticle sizes calculated using self-consistent regularization method applied to nitrogen adsorption data.